Analysis of causality relationship between the composite stock price index (CSPI) Jakarta with large companies in Indonesia - Puspa Liza, Ghazali; Sukono, .; Soeryana, E; Belladina, N; Santoso, A; Bon, A.T. (2019)
The process of globalization lately, causes most countries pay great attention to the capital market, because it has an important and strategic role for a country's economic security. The existence of the global economic crisis has a significant impact on the condition of the Indonesian capital market. Capital market movements can be seen from the ups and downs of stock prices recorded in an index movement or better known as the Composite Stock Price Index (CSPI). This paper intends to examine the causality relationship between the Indonesian stock market and the Jakarta CSPI. The aim is to investigate the causality of the returns of large companies in Indonesia with the movement of CSPI stocks. The method used is granger causality test with Vector Autoregression (VAR) modeling and volatility modeling using GARCH model approach. Causality test results show that there is a direct relationship that affects and is influenced by the CSPI, and the relationship that affects each other between the company's stock market and the movement of the CSPI.